Tropical and subtropical fruits : postharvest physiology, processing and packaging - Siddiq, Muhammad, 1957- (Wiley-Blackwell, 2012)
Tropical and sub-tropical fruits have gained significant importance in global commerce. This book examines recent developments in the area of fruit technology including: postharvest physiology and storage; novel processing technologies applied to fruits; and in-depth coverage on processing, packaging, and nutritional quality of tropical and sub-tropical fruits. This contemporary handbook uniquely presents current knowledge and practices in the value chain of tropical and subtropical fruits world-wide, covering production and post-harvest practices, innovative processing technologies, packaging.